Evaluation of patient reporting of adverse drug reactions to the UK ‘Yellow Card Scheme’: literature review, descriptive and qualitative analyses, and questionnaire surveys - Avery, Anthony; Anderson, Claire; Bond, C.M.; Fortnum, H.; Gifford, A.; Hannaford, P.C.; Hazell, L.; Krska, J.; Lee, A.J.; McLernon, D.J.; Murphy, Elizabeth; Shakir, S.; et al. (NIHR HTA, 2011)
Background: The monitoring of adverse drug reactions (ADRs) through pharmacovigilance is vital to patient safety. Spontaneous reporting of ADRs is one method of pharmacovigilance, and in the UK this is undertaken through the Yellow Card Scheme (YCS). Yellow Card reports are submitted to the Medicines and Healthcare products Regulatory Agency (MHRA) by post, telephone or via the internet. The MHRA electronically records and reviews information submitted so that important safety issues can be detected. While previous studies have shown differences between patient and healthcare professional (HCP) reports for the types of drugs and reactions reported, relatively little is known about the pharmacovigilance impact of patient reports. There have also been few studies on the views and experiences of patients/consumers on the reporting of suspected ADRs. Objectives: To evaluate the pharmacovigilance impact of patient reporting of ADRs by analysing reports of suspected ADRs from the UK YCS and comparing reports from patients and HCPs. To elicit the views and experiences of patients and the public about patient reporting of ADRs. Design: (1) Literature review and survey of international experiences of consumer reporting of ADRs; (2) descriptive analysis of Yellow Card reports; (3) signal generation analysis of Yellow Card reports; (4) qualitative analysis of Yellow Card reports; (5) questionnaire survey of patients reporting on Yellow Cards; (6) qualitative analysis of telephone interviews with patient reporters to the scheme; (7) qualitative analysis of focus groups and usability testing of the patient YCS; and (8) national omnibus telephone survey of public awareness of the YCS. Participants: Patients (n = 5180) and HCPs (n = 20,949) submitting Yellow Card reports from October 2005 to September 2007. Respondents to questionnaire survey (n = 1362). Participants at focus groups and usability testing sessions (n = 40). National omnibus telephone survey (n = 2028). Setting: The literature review included studies in English from across the world. All other components included populations from the UK; the omnibus survey was restricted to Great Britain. Interventions: None. Main outcome measures: Characteristics of patient reports: types of drug and suspected ADR reported; seriousness of reports; and content of reports. The relative contributions of patient reports and of HCP reports to signal generation. Views and experiences of patient reporters. Views of members of the public about the YCS, including user-friendliness and usability of different ways of patient reporting. Public awareness of the YCS. Suggestions for improving patient reporting to the YCS. Results: Compared with HCPs, patient reports to the YCS contained a higher median number of suspected ADRs per report, and described reactions in more detail. The proportions of reports categorised as ‘serious’ were similar; the patterns of drugs and reactions reported differed. Patient reports were richer in their descriptions of reactions than those from HCPs, and more often noted the effects of ADRs on patients’ lives. Combining patient and HCP reports generated more potential signals than HCP reports alone; some potential signals in the ‘HCP-only’ data set were lost when combined with patient reports, but fewer than those gained; the addition of patient reports to HCP reports identified 47 new ‘serious’ reactions not previously included in ‘Summaries of Product Characteristics’. Most patient reporters found it fairly easy to make reports, although improvements to the scheme were suggested, including greater publicity and the redesign of web- and paper-based reporting systems. Of the public, 8.5% were aware of the YCS in 2009. Conclusions: Patient reporting of suspected ADRs has the potential to add value to pharmacovigilance by: reporting different types of drugs and reactions than those reported by HCPs; generating new potential signals; and describing suspected ADRs in enough detail to provide useful information on likely causality and impact on patients’ lives. These findings suggest that further promotion of patient reporting to the YCS is justified, along with improvements to existing reporting systems. In order of priority, future work should include further investigation of: (1) the pharmacovigilance impact of patient reporting in a longer-term study; (2) the optimum approach to signal generation analysis of patient and HCP reports; (3) the burden of ADRs in terms of impact on patients’ lives; (4) the knowledge and attitudes of HCPs towards patient reporting of ADRs; (5) the value of using patient reports of ADRs to help other patients and HCPs who are seeking information on patient experiences of ADRs; and (6) the impact of increasing publicity and/or enhancements to reporting systems on the numbers and types of Yellow Card reports from patients.